Occupational chemical burns: a 2-year experience in the emergency department - Touzopoulos, Panagiotis (Dove Medical Press, 2011)
Chemical burn injuries are a result of exposure to acid, alkali, or organic compounds. In this retrospective study, a total of 21 patients suffering occupational chemical burns, came to the emergency room at the University General Hospital of Alexandroupolis, from 2008 to 2010; 76.2% were workers, 19% were farmers, and 4.8% were desk officers. The majority of burns were due to exposure to acid (61.9%). Upper extremities were the most frequently injured area followed by the lower extremities and thorax. None of the patients needed further hospital care, but in the follow-up, four of the patients suffered keloid. Proper surgical treatment at the emergency room decreases the length of hospital stay for patients who suffer chemically induced burns.